Utility of serum Aspergillus-galactomannan antigen to evaluate the risk of severe acute exacerbation in chronic obstructive pulmonary disease. - Katsuhiro Yoshimura; Yuzo Suzuki; Yusuke Inoue; Koji Nishimoto; Kazutaka Mori; Masato Karayama; Hironao Hozumi; Kazuki Furuhashi; Noriyuki Enomoto; Tomoyuki Fujisawa; Yutaro Nakamura; Naoki Inui; et al. (PLoS ONE, 2018)
Background Recent studies have shown that the microbiome, namely Aspergillus species, play a previously unrecognized role in both stable and exacerbated chronic obstructive pulmonary disease (COPD). Galactomannan is a major component of the Aspergillus cell wall that has been widely used as a diagnostic marker. Objectives To explore whether serum levels of Aspergillus-galactomannan antigen could be used to evaluate the risk of severe acute exacerbation of COPD (AE-COPD). Methods We measured the Aspergillus-galactomannan antigen levels of 191 patients with stable COPD, and examined its clinical relevance including AE-COPD. Results There were 77 (40.3%) patients who were positive for serum Aspergillus-galactomannan antigen (≥0.5). High Aspergillus-galactomannan antigen level (≥0.7) was associated with older age and presence of bronchiectasis and cysts on computed tomography images. Compared to patients with low Aspergillus-galactomannan antigen level (<0.7), patients with high Aspergillus-galactomannan antigen level had significantly higher incidence of severe AE-COPD (P = 0.0039, Gray's test) and respiratory-related mortality (P = 0.0176, log-rank test). Multivariate analysis showed that high Aspergillus-galactomannan antigen level was independently associated with severe AE-COPD (hazard ratio, 2.162; 95% confidence interval, 1.267-3.692; P = 0.005). Conclusion Serum Aspergillus-galactomannan antigen was detected in patients with COPD, and elevated serum Aspergillus-galactomannan antigen was associated with severe AE-COPD.